Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve by completing the square x^2-6x-4=0

Sagot :

Answer:

x = 3 ± [tex]\sqrt{13}[/tex]

Step-by-step explanation:

x² - 6x - 4 = 0 ( add 4 to both sides )

x² - 6x = 4

To complete the square

add ( half the coefficient of the x- term)² to both sides

x² + 2(- 3)x + 9 = 4 + 9

(x - 3)² = 13 ( take square root of both sides )

x - 3 = ± [tex]\sqrt{13}[/tex] ( add 3 to both sides )

x = 3 ± [tex]\sqrt{13}[/tex]

Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.